An introduction to a mathematical treatment of economics - Archibald, G. C.; Lipsey, Richard G. (London: Weidenfeld & Nicolson, 1967)
This book is addressed to two distinct groups of students. The first group consist of those who have completed O-level mathematics, who may have disliked it, and have almost certainly forgotten much of it, but who have already completed an introductory course in economics and are going on in economics. The second group consists of students who have taken A-level mathematics, who are possibly taking a first-year university course in mathematics, who are currently studying introductory economic theory, and who wish to follow a more formal and rigorous treatment of some of the theory than they can find in the standard introductory text-book.
With answers to exercises.
Includes bibliographical references and index.
rpm 03/07/2017
Loans
Keywords: Economics, Mathematical; Economics-Study and teaching